Impact of the COVID-19 pandemic on Malaysian labour market and policy responses - Lim, Beatrice Fui Yee (The Japan Institute for Labour Policy and Training (JILPT), 2022)
The COVID-19 pandemic has affected labour markets around the world, resulting in job losses and reduction in working hours. According to the most recent global estimates and country-level data, the crisis has resulted in a severe employment shortfall that has persisted in most nations (International Labour Organization 2021). A report from the ILO estimates that the global employment-to-population ratio decreased from 57.6% in 2019 to 54.9% in 2020 (Ibid.). In Malaysia, there is a significant decline in employment and a rise in unemployment rate. The gross domestic product (GDP) in 2020 contracted by 5.3% as compared to 4.3 percent point growth in 2019. As of 11 February 2022, a total of 2,956,332 cases and 32,065 death were reported in Malaysia (Johns Hopkins University and Medicine 2022). The pandemic is not only a public health crisis, but it has socioeconomic consequences. This unprecedented crisis and the various disease mitigation measures that have been implemented in many countries, including Malaysia, have further affected the country’s economic activities. There are significant reductions in income, reduced productivity, a rise in unemployment, loss of life, business closures, trade disruptions and reductions in transportation, services, and manufacturing activities (Pak et al. 2020) as well as risk of increased poverty and long-term systemic damage to our socio-economic fabric (Ministry of Finance Malaysia 2020). The Malaysian economy is reported to lose an estimated RM2 billion1 every day while restricted movement was imposed. In the process of recovery, the Government launched the 6R Strategy, comprising six stages of Resolve, Resilient, Restart, Recovery, Revitalise and Reform (Ibid.).